Effect of oral healthcare education on knowledge, attitude and skills of care home nurses: a systematic literature review. Issue 1 (30th July 2013) - de, Kersti H.M.E.; Vanobbergen, Jacques N.O.; van der, Gert‐Jan; De, Luc M.J.; Schols, Jos M.G.A.; de, Cees
Abstract Objectives To systematically review the literature on the effect of providing oral healthcare education to care home nurses on their oral healthcare knowledge and attitude and their oral hygiene care skills. Methods A literature search was obtained for relevant articles on oral healthcare education of nurses in care homes, using five electronic retrieval systems and databases. The search was limited to human studies, articles published in English and articles published during the period January 1990 to December 2011. The methodological quality of an article was assessed on the basis of criteria published by the Cochrane Collaboration. For articles not meeting all methodological quality criteria, relevance criteria were used to determine how much scientific evidence could be assigned to the study findings. Results In accordance with the methodological quality criteria, two randomized controlled trials were included. Additionally, four studies were included after determining the scientific evidence of the study findings. The studies included revealed some scientific evidence and indications that an oral healthcare education programme for care home nurses may improve the nurses' oral healthcare knowledge and attitude. Any effect of oral healthcare education to care home nurses' oral hygiene care skills could not be determined. Conclusions Oral healthcare education may have a positive effect on care home nurses' oral healthcare knowledge and attitude and on care home residents' oral hygiene, whereas any effect on care home nurses' oral hygiene care skills could not be found.